Analisis Gangguan Dalam Komunikasi Transendental: Perspektif Yoga Darsana - I Nengah Lestawi; Gupta, Endy; Ida Bagus Ketut Mantra (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2024)
Transcendental communication is intrapersonal communication that occurs between humans and God. In general, this communication is conducted in various forms, i.e., puja-mantra or prayer, meditation, and other religious and spiritual practices. However, often, the fundamental connectedness that is a fundamental requirement in transcendental communication fails to be actualized. From the perspective of yoga darśana, the failure of true transcendental communication to be actualized is often caused by disturbances in the form of mind modifications (vṛtti) that cause one's consciousness (citta) to spread everywhere and become attached to sense objects. These disturbances must be removed; hence the self could be in a suitable state to establish true connectedness with Īśvara. The discipline of yoga in the form of aṣṭāṅgayoga or ṣaḍaṅgayoga, carrying it out with the spirit of abhyāsa and vairāgyā, is a discipline that can support oneself in eliminating various disturbances. Therefore, one can build one's decent state to establish a perfect connectedness with Īśvara. When the “state” of oneself is free from all forms of disturbance, then true transcendental communication can be actualized. This research uses qualitative methods and the data collected through literature review.